SMALL-SCALED ENVIRONMENTAL CHANGES: INDICATIONS FROM STABLE ISOTOPES OF GASTROPODS (EARLY MIOCENE, KORNEUBURG BASIN, AUSTRIA) - Latal Ch.; Piller W.E.; Harzhauser M. (My University, 2006)
The Korneuburg Basin, with mainly upper Lower Miocene (Karpatian) sediment filling, is divided by the Mollmannsdorf–Obergänserndorf Swell into two sub-basins characterised by different environmental settings. Paleoecological data indicate a marine northern part and a mainly estuarine southern part. Nevertheless, short-termed marine ingressions from the north allowed marine faunas (ostracods, molluscs, and echinoids) to temporarily settle the southern part of the basin. The carbon and oxygen isotopic composition of gastropod shells from these different environmental settings were investigated. Highest δ18O and δ13C values are found in Turritella shells from the northern part of the basin, and in Turritella shells from layers interpreted as a marine ingression in the south. Generally, components of the mudflat fauna (Tympanotonos cinctus, Granulolabium bicinctum, Terebralia bidendata, and Ocenebra crassilabiata) have slightly lower isotope values. Considerable freshwater influx in the southern part is documented by abundant freshwater genera such as Melanopsis, which show low carbon and oxygen isotope values. Data of identical taxa, especially Turritella and Granulolabium, reflect a trend from higher isotope values at the marine northern part to slightly lower values in the mainly estuarine southern part of the basin. Differences in δ18O between the marine and the estuarine assemblages are interpreted to be caused by changes in salinity and isotopic composition of ambient water rather than by temperature. Paleotemperature estimates derived from oxygen isotope data are in good agreement with existing paleoclimatic proxies for the Korneuburg Basin. Hence, an annual range of the sea-surface temperature from 13 to 26°C can be predicted within that protected basin.
Keywords: STABLE ISOTOPES; GASTROPODS; PALEOECOLOGY; PALEOCLIMATE; SALINITY; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен